2020
DOI: 10.12944/crnfsj.8.3.24
|View full text |Cite
|
Sign up to set email alerts
|

Application of Astaxanthin and its Lipid Stability in Bakery Product

Abstract: The application of astaxanthin is not widely studied especially on its uses and relationship toward lipid stability in food products. Therefore, this study was aimed to determine the antioxidant activity of astaxanthin and evaluate its lipid stability, physicochemical and sensory properties of astaxanthin formulated cookies. The antioxidant activity of astaxanthin was analyzed using DPPH, HRSA and FRAP assays. Meanwhile, lipid stability including peroxide value (PV), p-anisidine value (P-aV) and TOTOX value wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…AL‐Tarifi et al. (2020) [27] hypothesized that this is due to the presence of a conjugated double bond in the middle of the ASX compound, which thus acts as an active antioxidant through electron donation to promote the formation of highly stable non‐radical products. Ren et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AL‐Tarifi et al. (2020) [27] hypothesized that this is due to the presence of a conjugated double bond in the middle of the ASX compound, which thus acts as an active antioxidant through electron donation to promote the formation of highly stable non‐radical products. Ren et al.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained are in accordance with the conclusions of the study by Sakayanathan et al (2018) [26] that ASX is able to quench higher number of radicals in both excited and ground state compared to AT. AL-Tarifi et al (2020) [27] hypothesized that this is due to the presence of a conjugated double bond in the middle of the ASX compound, which thus acts as an active antioxidant through electron donation to promote the formation of highly stable non-radical products. Ren et al (2021) [28] also concluded, that ASX and CRO may be effective in stress-induced cellular redox imbalances in the human body.…”
Section: Ability Of Test Substance To Reduce Metal Ionsmentioning
confidence: 99%
“…It was reported that astaxanthin, through its diverse antioxidant activities, possesses an organoleptic quality that aids in diet consumption of animals 43 . Studies have also shown that astaxanthin helped to stabilize lipid in food products, thereby preventing any rancidity that could render foods unfit for consumption 55 . Wang et al 56 .…”
Section: Resultsmentioning
confidence: 99%